Comparison of endoscopic submucosal dissection and surgical resection for treating gastric subepithelial tumours. (3rd May 2016) - Soh, Jae Seung; Kim, Ja Kyung; Lim, Hyun; Kang, Ho Suk; Park, Ji Won; Kim, Sung Eun; Moon, Sung Hoon; Kim, Jong Hyeok; Park, Choong Kee; Cho, Ji Woong; Lim, Man Sup; Kim, Kyoung Oh
Abstract: Objective For subepithelial tumours (SETs) of the stomach, surgical resection is the gold standard treatment. With the recent advent of endoscopic resection techniques and devices, endoscopic submucosal dissection (ESD) has been considered as an alternative treatment for SETs. The aim of our study was to evaluate the clinical outcomes of ESD for treating gastric SETs compared with surgical resection.Methods Between January 2006 and September 2014, 55 patients with gastric SETs (13 gastrointestinal stromal tumours (GISTs), 27 leiomyomas, and 15 others) were treated by ESD and 27 patients (19 GISTs, two leiomyomas, and six others) underwent surgical resection. We retrospectively reviewed the therapeutic outcomes, procedure-related complications, post-procedure hospital stays, and medical costs of the two groups.Results The complete resection rate of the ESD group was lower than that of the surgery group (81.8% vs. 100%, p = 0.026). Although the incidence of complications that occurred with ESD was higher than that associated with surgical resection, there were no significant between-group differences (12.5% vs. 3.7%, p = 0.261), and all complicated cases were successfully treated without mortality. The ESD group had significantly shorter post-procedural hospital stays (median five days vs. eight days, p = 0.034) and lower medical costs (median 2374 vs . 4954, p <0.001) than the surgery group. There were no recurrences in either group during the follow-up period.Conclusions ESD is an efficient treatment tool for gastric SETs in selected patients. Additionally, ESD has the advantages of shorter hospital stays and lower medical costs compared with surgery.